2016
DOI: 10.1016/j.scitotenv.2016.05.093
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sediment sources in a lowland agricultural catchment pond using 137Cs activities and radiogenic 87Sr/86Sr ratios

Abstract: Soil erosion often supplies high sediment loads to rivers, degrading water quality and contributing to the siltation of reservoirs and lowland river channels. These impacts are exacerbated in agricultural catchments where modifications in land management and agricultural practices were shown to accelerate sediment supply. In this study, sediment sources were identified with a novel tracing approach combining cesium ((137)Cs) and strontium isotopes ((87)Sr/(86)Sr) in the Louroux pond, at the outlet of a lowland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 96 publications
(114 reference statements)
0
25
0
Order By: Relevance
“…A previous fingerprinting approach study based on the 137 Cs activity performed in this catchment estimated that the subsurface source (bank erosion) contributed 18% (σ 1%) of the pond sediment over the last 10 years (Le Gall et al, ). This result is slightly different than the contribution estimated in this study (27% to 30%) but still on the same order of magnitude.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous fingerprinting approach study based on the 137 Cs activity performed in this catchment estimated that the subsurface source (bank erosion) contributed 18% (σ 1%) of the pond sediment over the last 10 years (Le Gall et al, ). This result is slightly different than the contribution estimated in this study (27% to 30%) but still on the same order of magnitude.…”
Section: Resultsmentioning
confidence: 96%
“…Globally, streams are commonly being recognized as primary sources of sediment to streams and rivers (e.g., Laceby, ). Recent studies in an intensively farmed watershed have found that human‐altered stream channels are a minor component of net sediment delivery to a 52 ha pond (Foucher et al, Le Gall et al, ). Based on historic channel cross section surveys, the volume of material eroded from stream banks is quantified at different spatial and time scales: The annual volume of material eroded from stream banks along a small headwater stream (1,400‐m long) during one hydrological year has been estimated using erosion pin data. Long‐term bank erosion has been estimated by comparing elevation data obtained in 2013 from differential global positioning system (DGPS) acquisition combined with aerial LiDAR survey to three‐dimensional historical plans dating back to the stream redesign in 1944.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distribution modelling approach was used to quantify the relative contribution of each source to sediment through the minimization of the mixing model difference (MMD) (Laceby & Olley, ; Le Gall et al ., ): MMD=italicABS()()Ci()truetrue∑s=1mSsixstrue/Ci+italicABS()()Cr()()truetrue∑s=1mSsrWsxstrue/()truetrue∑s=1mWsxstrue/Cr Where: C i is the concentration of element i in the suspended sediment, m is the number of sources in the catchment; S si is the concentration of element i in source ( s ); C r is the strontium isotopic ratio ( r ) in the suspended sediment; S sr is the strontium isotopic ratio ( r ) in source ( s ); W s is the strontium concentration in source (s), which is used to weight the strontium isotopic ratios; MMD is the mixing model difference; and x s is the proportional contribution of source ( s ), which is modelled as a truncated normal distribution (0 ≤ x s ≤ 1) with a mixture mean ( μ m ) and a standard deviation (SD) ( σ m ). Absolute values ( ABS ) are summed in Equation .…”
Section: Methodsmentioning
confidence: 99%
“…Three combinations of particulate matter parameters were modelled: 1) TN and d 15 N (the N model); 2) TOC and d 13 C (the C model); 3) all 4 properties (the C þ N model). These combinations were used to quantify relative source contributions with a concentration weighted distribution modelling approach (Laceby et al, 2015b;Le Gall et al, 2016):…”
Section: Statistical Analyses and Source Modellingmentioning
confidence: 99%